Probing the role of the ceramide acyl chain length and sphingosine unsaturation in model skin barrier lipid mixtures by (2)H solid-state NMR spectroscopy - Stahlberg, Sören; Školová, Barbora; Madhu, Perunthiruthy K; Vogel, Alexander; Vávrová, Kateřina; Huster, Daniel (Langmuir, 2015)
We investigated equimolar mixtures of ceramides with lignoceric acid and cholesterol as models for the human stratum corneum by differential scanning calorimetry and (2)H solid-state NMR spectroscopy. Our reference system consisted of lignoceroyl sphingosine (Cer[NS24]), which represents one of the ceramides in the human stratum corneum. Furthermore, the effect of ceramide acyl chain truncation to 16 carbons as in Cer[NS16] and the loss of the C4 trans double bond as in dihydroceramide Cer[NDS24] were studied. Fully relaxed (2)H NMR spectra were acquired for each deuterated component of each mixture separately, allowing the quantitative determination of the individual lipid phases. At skin temperature, the reference system containing Cer[NS24] is characterized by large portions of each component of the mixture in a crystalline phase, which largely restricts the permeability of the skin lipid barrier. The loss of the C4 trans double bond in Cer[NDS24] leads to the replacement of more than 25% of the crystalline phase by an isotropic phase of the dihydroceramide that shows the importance of dihydroceramide desaturation in the formation of the skin lipid barrier. The truncated Cer[NS16] is mostly found in the gel phase at skin temperature, which may explain its negative effect on the transepidermal water loss in atopic dermatitis patients. These significant alterations in the phase behavior of all lipids are further reflected at elevated temperatures. The molecular insights of our study may help us to understand the importance of the structural parameters of ceramides in healthy and compromised skin barriers.
Keywords: biologické modely; deuterium; Models, Biological; Magnetic Resonance Spectroscopy; Permeability; Fatty Acids; mastné kyseliny; Ceramides; Epidermis; epidermis; Humans; Deuterium; ceramidy; Cholesterol; permeabilita; lidé; magnetická rezonanční spektroskopie; cholesterol